(3eQBI GdReGf aj JGQjN GdCYjGfs - (3jhSa Hf pbrRoChrZpdj (B- (3Ch bRZdj (B- (3GHf YHO Gddg, CHh GdeXaQ, TeS GdOjf, SHW CHj GdaQL GHf GdLhRj,J (B654 (3g` s
(3ChdgG (B:s
(3bHjd GdcdGe Ydi NdGaI GdhdjO Hf YHOGdedc SfI (B96 (3g` s
(3BNQgG (B:s
(3BNQ SfI (B121 (3g` s
(3eLdO ef SfI (B96 (3g Edi BNQ SfI (B121 (3g`s
(3fSNI SGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B246 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B324s
Keywords: (3GdJGQjNs